Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd007510.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin for masseter hypertrophy

Abstract: We were unable to identify any randomised controlled trials on the efficacy of intra-masseteric injections of botulinum toxin for people with bilateral benign masseter hypertrophy. The absence of high level evidence for the effectiveness of this intervention emphasises the need for well-designed, adequately powered, randomised controlled clinical trials (RCTs) and controlled clinical trials (CCTs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 32 publications
0
27
0
1
Order By: Relevance
“…Unloading of the mandible using BTX has been suggested as a technique to allow immediate placement of dental implants [6], but the present results show that such unloading might accelerate bone loss, a counterproductive outcome. An even greater concern is the persistent loss of bone microstructure at the mandibular condyle.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 65%
See 1 more Smart Citation
“…Unloading of the mandible using BTX has been suggested as a technique to allow immediate placement of dental implants [6], but the present results show that such unloading might accelerate bone loss, a counterproductive outcome. An even greater concern is the persistent loss of bone microstructure at the mandibular condyle.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 65%
“…In addition to injecting facial muscles to relax wrinkled skin and relieve blepharospasm, BTX is used to inactivate the major muscles of mastication, particularly the large masseter muscles. One common reason for injecting BTX into asymptomatic masseters is cosmetic, to change a square-angled face into a more oval one by causing the muscles to atrophy; patients receiving this treatment are predominantly young and female and typically receive repeat injections [4-6]. The masseters are also paralyzed with BTX when it is considered desirable to unload the jaws [7-9] and in the hope of alleviating facial pain involving the temporomandibular joint (TMJ) [10], although load reduction has not been proven and relief of pain is marginal [10-12].…”
Section: Introductionmentioning
confidence: 99%
“…Botulinum toxin type A injection is reported to be a safe and effective treatment modality in e650 orofacial dystonies, sialorrhea, frey's syndrome, muscle hypertrophies, etc (6)(7)(8)(9). Botulinum toxin type A is a powerful neurotoxin which is produced by the anaerobic organism Clostridium botulinum and when injected into a muscle causes interference with the neurotransmitter mechanism producing selective paralysis and subsequent atrophy of the muscle (10,11). The aim of this report is to present two cases of masseter muscle hipertrophy which were treated with botulinum toxin type A injection.…”
Section: Introductionmentioning
confidence: 99%
“…1,[15][16][17][18][19][20][21][22][23][24][25][26][27] Current literature does not offer comprehensive reviews of the time, prognosis, or recovery process of related complications, and the Cochrane review in 2009 and 2013 reported an insufficient amount of high level evidence to accurately assess the efficacy and safety of toxin injections for masseter hypertrophy. 28,29 A previous report by the authors in 2018 outlined masseter toxin injection complication rates from 2036 treatments, 30 though it was limited in scope to a single clinic. This literature review is an attempt by the authors to unify and consolidate if possible the nature of adverse events associated with this procedure, and provide clinicians with a comprehensive understanding of possible complications.…”
mentioning
confidence: 99%